THE DETERMINANTS OF JOB STRESS AND ITS INFLUENCE ON EMPLOYEES’ WELL-BEING - Nurul Athirah Sukor; Norhanisah Mohd Zaide; Nursyazwani Samsul; Nor Syahidah Azman; Kamarul Haizam Samli; Siti Nurul Akma Ahmad (International Journal of Accounting, Finance and Business, 2022)
This article is discussing about job stress and how it has been linked to well-being amongst people working in different working environments. The previous studies on the factors of work stress and how it might impact the well-being of employees is reviewed in this research article. The review clarifies the concept of workplace stress, as well as the individual wellbeing and working characteristics of employees. Job stress is indeed a major contributor to organizational poor performance and lowers job satisfaction. This study aims to investigate the determinants factors of job stress and how its influence one's well-being. Based on the reviews, workload, longer working hours, lack the reciprocity of fairness are the most common contributing factors for job stress. This review will benefit to the manager and organization to achieve their organizational goals by providing an intervention program of work stress among employees.